School culture as a determinant of implementation of the independent curriculum - Heryanti, Yudina Tri; Raharjo, Tri Joko; Yulianto, Arief (Universitas Negeri Semarang, 2023)
Each organization presents how its members live. This research aims to find out and understand organizational culture in the implementation of the Independent Curriculum, what factors shape organizational culture, strategies for implementing independent curriculum planning based on school culture. This research uses a qualitative research method, a case study approach. Data collection techniques in this research are in three ways, namely observation, interviews and documents. Data validity techniques include extension techniques, persistence in in-depth observation, 3 types of triangulation, and conducting member checks. Data analysis techniques using data collection, data reduction, data presentation, and drawing/verification conclusions. Based on the results of this research, organizational culture at Nasima Junior High School, Semarang, based on Hofstede, consists of six dimensions of organizational culture, namely Power Distance, Group Attachment, Gender Association, Uncertainty Avoidance, Time Orientation, and Indulgence. The influence of organizational culture in implementing the Independent Curriculum at Nasima Junior High School, Semarang is that organizational culture can encourage an open attitude towards change on supporting the implementation of the Independent Curriculum, commitment to active and creative learning, appreciation for Creativity and Innovation., Factors that shape organizational culture at Nasima Junior High School Semarang can vary and be influenced by various elements. There are several strategies in planning the implementation of the independent curriculum at Nasima Junior High School. This strategy begins with adapting school culture.